"It gives me a wake up call"—It is time to implement athlete health monitoring within the Para sport context. (21st December 2022) - Fagher, Kristina; Badenhorst, Marelise; Kunorozva, Lovemore; Derman, Wayne; Lexell, Jan
Abstract : Objectives: The aim of this study was to explore elite Para athletes' and coaches' perceptions of experiences of athlete health monitoring. Materials and Methods: This study used a qualitative design, applying a phenomenographical approach. Thirteen athletes and six coaches from two different socioeconomic contexts (the Swedish and South African Paralympic programs) participated. Data were collected through individual interviews focusing on athletes' and coaches' perceptions of experiences of athlete health monitoring within Para sport. Results: Three main themes were revealed: (i) the benefits of athlete health monitoring, (ii) the importance of implementation and adaptation of athlete health monitoring in the real‐world sports context, and (iii) barriers of athlete health monitoring. The perceptions were that regular monitoring can detect injuries early and thereby prevent them from progressing. Several participants highlighted the importance of monitoring factors beyond injury and illness, such as Para sport‐specific health issues. Athletes' experiences were that they started to reflect on their own health, which was interpreted as improvement in health literacy. Another perception was that athlete health monitoring only is conducted within the research context and that athletes are not followed up. The perception was that it is the sports federations' responsibility to monitor and provide support when needed. Lastly, data revealed differences in the possibilities of conducting monitoring, which was related to both socioeconomic factors and Para sport. Conclusion: Coaches and athletes see health monitoring as valuable and important in enhancing athlete health. However, to maximize the impact, the monitoring structure should be specific to the context and provide multidisciplinary support when needed.